TAHLIL MUHTAWA KITAB "AL-LUGHAH AL-'ARABIYAH" LI AL-SHAF AL-KHAMIS FI MALAYSIA - Wiaam Mohammad Syairozi (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2015)
This study aims to analyze and critique the textbook for students of the fifth year or second-year secondary high school at Malaysian Madrasa. And it adopted a researcher at the research on the descriptive and analytical approach imposed by the nature of the study from the description of the book and the collection of data and information. The results of this study have shown that suitable book details the secondary stage, either in terms of language or cultural content resulting in the content of the book with the book’s goals. The linguistic content of the book suitable for the secondary stage only in literacy and dialogue texts, because the level of texts is high according to high school students, in addition to the length of the text which is about two pages. The cultural content for the local culture are regarded as very adequate, but lacks the Arab culture, because it is very important to get to know the culture of the studied language.DOI: 10.15408/a.v2i2.2185